The Role of China's Household Registration System in the Urban-Rural Income Differential - Ernest Boffy-Ramirez; Soojae Moon (Institute of Labor Economics (IZA), 2017)
Together with the rapid growth of the Chinese economy, there has been a growing divide in the earnings of urban and rural residents. In this paper we focus on China's household registration system, or "hukou", as a potential source of the earnings gap. Using multiple waves of data from the Chinese Health and Nutrition Survey from 1993 through 2011, we take advantage of variation in hukou status generated by individual-level changes over time. Unlike previous studies, we are able to control for fixed individual-specific characteristics that determine earnings and focus specifically on estimating an urban hukou "premium". For estimates that do not account for time-invariant individual characteristics, urban hukou holders earn almost 30% more than rural hukou holders. After we account for individual-level fixed characteristics, the urban hukou premium drops to 6–8%. Our empirical evidence indicates that the hukou system is a notable component of the urban-rural earnings differential, but its importance should not be overstated. Given long-standing differences in access to government funding and social services between rural and urban populations, relaxing residency restrictions may not be a panacea for curbing rising income inequality.
Keywords: J30; J80; O15; R23; 330; hukou; migration; China; urban-rural income gap; inequality; labor market frictions